A cross sectional study to assess the prevalence of internet addiction and its relationship with personality traits in retirees in an urban field practice area of a medical college in Chennai, Tamil Nadu. - Aravindh, Bhuvanesh; Swetha, N. B.; Sujitha, P.; Munisingh, Abhilasha; Priya, Meena (Discover Public Health, 2026)
Background: Internet use has become increasingly common among older adults, including retirees. While digital engagement offers several benefits, excessive or poorly regulated use may lead to internet addiction, an issue that remains underexplored among the elderly, particularly in the Indian context. Objectives: To estimate the prevalence of internet addiction and examine its association with personality traits among retired older adults in Chennai, Tamil Nadu. Methods: A cross sectional study was carried out among 260 retired older adults residing in the urban field practice area of Sree Balaji medical college and hospital between November 2024 and November 2025. Participants were selected using purposive sampling. Internet addiction was assessed using the Compulsive Internet Use Scale (CIUS-7) and personality traits were measured using the Big Five Inventory (BFI-10). Data were analyzed using SPSS version 22, applying descriptive statistics, chi-square tests, logistic regression analysis, and correlation analysis, with statistical significance set at p < 0.05. Results: Among the 260 participants, 172 (66.2%) demonstrated normal internet use, 67 (25.8%) had problematic or compulsive internet use, and 21 (8.1%) were classified as being at risk of internet addiction. Age, marital status, education, previous occupation, income source, and living situation were significantly associated with internet addiction in univariate analysis. After multivariable adjustment, age, education level, and previous occupation remained significant predictors, while other variables were not significantly associated. Correlation analysis showed that conscientiousness was negatively associated with internet addiction whereas neuroticism and openness to experience were positively associated. Extraversion and agreeableness did not show significant associations. Conclusion: Internet addiction was identified as a relevant concern among retired elderly individuals and was influenced by both sociodemographic factors and personality traits. Early identification of retirees at risk and promotion of balanced internet use may help support mental well-being and healthy digital engagement in later life.